2009
DOI: 10.1038/labinvest.2009.56
|View full text |Cite
|
Sign up to set email alerts
|

CAR mediates efficient tumor engraftment of mesenchymal type lung cancer cells

Abstract: The coxsackie-adenovirus receptor (CAR) is a developmentally regulated intercellular adhesion molecule that was previously observed to be required for efficient tumor formation. To confirm that observation, we compared the tumorigenicity of clonally derived test and control cell subsets that were genetically modified for CAR. Silencing CAR in lung cancer cells with high constitutive expression reduced engraftment efficiency. Conversely, overexpressing CAR in lung cancer cells with low constitutive expression d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 65 publications
3
20
0
Order By: Relevance
“…Indeed, it was shown that CAR antagonizes the action of apoptosis inducing agents and in turn increases breast cancer cell survival (Bruning et al 2005). In a similar manner, as for lung cancer in which CAR silencing reduces tumor growth (Veena et al 2009), we show that CAR antibodies or CAR siRNA inhibit the estrogendependent growth of MCF-7 cells. We did not observe any sign of mortality when cells were treated with the CAR antibody, which suggests that CAR affects mainly cell proliferation than survival.…”
Section: Vindrieux Et Al: Car Is An Estrogen Receptor Targetsupporting
confidence: 67%
See 1 more Smart Citation
“…Indeed, it was shown that CAR antagonizes the action of apoptosis inducing agents and in turn increases breast cancer cell survival (Bruning et al 2005). In a similar manner, as for lung cancer in which CAR silencing reduces tumor growth (Veena et al 2009), we show that CAR antibodies or CAR siRNA inhibit the estrogendependent growth of MCF-7 cells. We did not observe any sign of mortality when cells were treated with the CAR antibody, which suggests that CAR affects mainly cell proliferation than survival.…”
Section: Vindrieux Et Al: Car Is An Estrogen Receptor Targetsupporting
confidence: 67%
“…Most studies have shown in bladder, cervical, ovary cancers, and glioma that CAR was repressing cell proliferation (Okegawa et al 2001, Kim et al 2003, Bruning & Runnebaum 2004, Huang et al 2005, Wang et al 2005, Zhang et al 2007, whereas others have shown mitogenic properties for CAR in lung cancer (Qin et al 2004, Veena et al 2009). The situation in breast cancer might be unique compared with other cancers.…”
Section: Vindrieux Et Al: Car Is An Estrogen Receptor Targetmentioning
confidence: 99%
“…To test the possible role of Daxx in disrupting Slug DNA-binding ability, we performed chromatin immunoprecipitation (ChIP) assays. In CL1–5 cells, Slug protein was recruited to the E-cadherin promoter and the CAR promoter, another validated Slug target gene39; however, this recruitment was decreased by co-expression of Daxx (Fig. 2f; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate a possible association, karyotype analysis was performed on the three MPE samples. Normal fibroblast GM 05399 and the lung cancer cell line NCI-H2122 were used as controls to represent non tumorigenic and immortalized tumor cell models [20][23]. All three MPE samples M-1, M-2 and M-3 showed extensive chromosomal changes with hyperdiploid number of chromosomes 83, 67, and 74 respectively (Figure 5B, D, F).…”
Section: Resultsmentioning
confidence: 99%
“…It was subsequently deposited into ATCC (NCI-H2122 [H2122] ATCC® CRL-5985™) [21]. The cell line is maintained in our laboratory in RPMI-1640 medium in presence of 10% FBS [22], [23]. Both the cell lines are publicly available.…”
Section: Methodsmentioning
confidence: 99%